Benefits and challenges of the public food procurement program: Perspectives of technicians and managers of family farmer organizations in Brazil - Panmela Soares; Suellen Secchi Martinelli; Elena Albero Atance; Rafaela Fabri; Vicente Clemente-Gómez; Mari Carmen Davó-Blanes; Suzi Barletto Cavalli (Heliyon)
Public food purchase programs are a useful tool for promoting food security through rural development, supporting family farmers, and encouraging sustainable and healthy food production. The study aimed to analyse the characteristics of family farmer organizations associated with the Brazilian Public Food Procurement (PFP) program and the opinion of technicians and managers of the organizations regarding the benefits and challenges of the program. A cross-sectional study was conducted through a structured questionnaire. The questionnaire contained questions regarding the characteristics of the organization and the food sales process, as well as the opinion about the benefits and challenges of PFP. The results were stratified according to the organization’s participation in the PFP. The chi-squared or Fisher’s exact test was applied. A total of 293 managers and technicians from family farmer organizations participated in the study. The majority of participants (71.7 %) reported their involvement in the PFP program. The study revealed that farmer organizations and public technical assistance agencies with larger memberships and employing conventional or mixed production methods were found to be more actively engaged in the PFP program across Brazil. Participants highlighted that direct sales under the program offer benefits to consumers, producers, and the environment. However, challenges identified include seasonal production constraints, bureaucratic hurdles in sales procedures, inadequate infrastructure for food storage and processing within farmer organizations, insufficient information from restaurants about purchasing opportunities, and a lack of support and technical assistance. These factors pose implementation challenges for the PFP program. While the PFP program shows promise in promoting direct sales and supporting local farmers, addressing the identified challenges will be crucial for its sustained success and broader adoption across different regions.